Rates of adverse events of antiretroviral therapy in women living with HIV/AIDS: a systematic review and meta-analysis - Cristiane de Cássia Bergamaschi; Luciane Cruz Lopes; Marcus Tolentino Silva; Lauren Giustti Mazzei; Maíra Ramos Alves; Jardel Corrêa de Oliveira; Fabiane Raquel Motter; Jorge Otávio Maia Barreto; Luis Phillipe Nagem Lopes; Rodrigo Suguimoto Iwami; Alexander Itria; Diogo Luis Scalco; et al. (BMJ Open, 2024)
Objective There is limited information regarding the incidence of treatment-related adverse events (AE) following antiretroviral therapy (ART) in women. So, this review aimed to describe the incidence of AE of ART in women living with HIV/AIDS.Design Systematic review and meta-analysis.Data sources Medline, Embase, Cochrane Library, Epistemonikos, Lilacs and Who Index, from inception to 9 April 2023.Eligibility criteria We included randomised controlled trials with at least 12 weeks of follow-up and evaluated AE of ART in women at any age living with HIV/AIDS, without restrictions on status, year or language of publication. We excluded post hoc or secondary analyses and open-label extensions without comparator, and trials involving pregnant or breastfeeding women or with a focus on coinfection with tuberculosis, hepatitis B or C. The primary outcomes were the incidence rate of participants with any clinical and/or laboratory AE related or not to ART and treatment discontinuation.Data extraction and synthesis Two independent reviewers extracted data and assessed the risk of bias using Cochrane’s risk of bias tool 2. We used Bayesian random-effects meta-analysis to summarise event rates. Results were presented as event rates per 1000 person-years (95% credibility intervals, 95% CrI). The pooled incidence rate per 1000 person-years adjusted for duration and loss to follow-up was estimated. We assessed the certainty of the evidence using Grading of Recommendations, Assessment, Development and Evaluation.Results A total of 24 339 studies were identified for screening, of which 10 studies (2871 women) met the eligibility criteria, with 11 different antiretrovirals (ARVs) regimens. Seven studies included exclusively women, while in the remaining three, the proportion of women ranged from 11% to 46%. Nine studies received industry funding. The pooled analysis showed a mean incidence rate of ART-related clinical and laboratory AE of 341.60 events per 1000 person-years (95% CrI 133.60–862.70), treatment discontinuation of 20.78 events per 1000 person-years (95% CrI 5.58–57.31) and ART-related discontinuation of 4.31 per 1000 person-years (95% CrI 0.13–54.72). Summary estimates were subject to significant uncertainty due to the limited number of studies and sparse data. The certainty of the evidence was graded as very low for all outcomes assessed.Conclusion Existing randomised trials do not provide sufficient evidence on the incidence rates of safety outcomes from antiretroviral treatment in women living with HIV/AIDS. Large comparative studies in well-characterised populations are needed to provide a more comprehensive landscape of the safety profile of these ARV therapies in women with HIV/AIDS.PROSPERO registration number CRD42021251051.